Contraceptive Use among Slum Women in Slums of Dhaka City - Akter, Rafia (American International Journal of Social Science Research, 2020)
Bangladesh has experienced a dramatic increase in contraceptive use and a sensational decline in fertility over 3 decades since its independence. The family planning program (FPP) in Bangladesh has been considered a success story in a setting without much socio-economic development. With the concerted effort of the Government of Bangladesh (GOB) and Non-Governmental Organizations (NGOs), women are becoming aware of physical health; (Icddr,b). In this context, a study has conducted to unveil the scenario of using contraception in the slum area of Dhaka City. In this research, 101 respondents were selected from two selected slums of Dhaka city. This study examines the use of contraceptives among the slum women. Findings revealed that respondents age 15-20) around 8.6% prefer an oral pill, 2.5% prefer IUD, 6.2% prefer condom (husband’s method) and 4.9% prefer injectable. Respondents aged within (21-25) around 19.8% prefer oral pill, 3.7% prefer IUD, 6.2% prefer condom (husband’s method) and 7.4% prefer injectable. Respondents age (above 25) around 21.0% prefer oral pill, 1.2% prefer IUD, 1.2% prefer condom (husband’s method) and 17.3% prefer injectable. In total, around 49.4% prefer an oral pill, 7.4% prefer IUD, 13.6% prefer condom and 29.6% prefer injectable. Women’s education, exposure to mass media, current work status husband’s working status, age of marriage, decision-making rights, religious restriction are the important determinants of contraceptive use among slum women.